Protocolo de enfermagem para avaliação e tratamento de lesão por pressão em pessoas idosas hospitalizadas - Albuquerque, Fernanda Kelly Oliveira de (2025)
Introduction: The incidence of pressure injuries increases proportionally to the presence of risk factors, with advanced age being one of the most relevant. In elderly individuals, these injuries are more likely to develop into infections and sepsis, which prolongs hospitalization time, increases healthcare costs, and increases mortality rates. Given this scenario, it is essential to implement healthcare instruments and technologies that support nurses' work in the assessment and treatment of these injuries in hospitalized elderly individuals. Objectives: To investigate, in the scientific literature, evidence related to nursing interventions for the assessment and treatment of pressure injuries in hospitalized elderly people and to develop a nursing protocol for the assessment and treatment of pressure injuries in hospitalized elderly people. Method: This is a methodological study developed in two stages. The first consisted of a scoping review conducted according to the Joanna Briggs Institute methodology, with searches carried out between March and April 2024 in the following databases: Medical Literature Analysis and Retrieval System, Excerpta Medica DataBASE, Latin American and Caribbean Literature in Health Sciences, National League for Nursing and American Nurses Association, Scopus, Cochrane Library, Web of Science, Banco de Dados em Enfermagem - Bibliografia Brasileira, ProQuest Dissertations & Theses Global, and Google Scholar. No language or publication period restrictions were applied. The review protocol followed the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews. The second stage involved the development of the nursing protocol, based on the evidence identified in the review and the most up-to-date references on the topic. Results and Discussion: Eighteen studies published between 1995 and 2023 were selected, the majority of which were developed in the United States (22.2%) and Japan (22.2%). The predominant language was English (94.4%) and 33.3% of the studies had a retrospective design. The analysis resulted in two thematic categories: (1) Interventions, assessment and nursing management systems for pressure injuries and (2) Products and technologies applied to the treatment of pressure injuries. The need for the use of validated scales for monitoring healing and therapeutic assessment was highlighted, as well as the importance of implementing preventive strategies even after the onset of the injury, reinforcing the need for standardization of procedures. The protocol developed includes its purpose, justification, scope, definitions and classification of injuries, as well as guidelines for assessment, treatment and instructions for hospital discharge. Final considerations: The application of the protocol developed may contribute to the planning and adaptation of interventions to the individual needs of the elderly person, promoting greater autonomy and safety in clinical decision-making, in addition to favoring the standardization of care provided by the nursing team.